CEEC’s-China Mechanism of Cooperation and the Belt and Road Initiative: From Idea to Institutionalisation – Six Years Later - Duško Dimitrijević; Nikola Jokanović (Međunarodni Problemi)
The paper analyzes the process of institutionalization of intergovernmental cooperation and coordination of state policies through the mechanism of cooperation between the countries of Central and Eastern Europe (CEEC) and China, known in the public as “16 + 1” (i.e., “17 + 1” starting in 2019). Through an eclectic picture of the development of contemporary international relations, the authors indicate in a methodologically accessible manner that this mechanism of cooperation is a significant impetus for the development of international relations. Since China has taken a dominant role in redefining the Global Management System, whose goals are balanced and sustainable international development, to achieve them, China has identified certain ideological frameworks that are present in its foreign policy through the Belt and Road Initiative. Through this Initiative, China seeks to achieve the broader goals of the New Silk Road development strategy, which not only determines the directions of China’s internal development, but provides guidance for its strategic cooperation with neighbouring countries as well as with countries on other continents. Consequently, the mechanism itself thus plays an important role in strengthening China’s foreign policy position, not only with respect to CEEC, but also with respect to other European countries, including the EU as a whole.